Tilapia Cultivation Training Using the Biofloc System Impacts on Increasing Community Income in Paccerakkang Village, Makassar City - Mardiana ibrahim; Mardia; Muhammad Yusuf (www.amertainstitute.com, 2025)
Tilapia fish cultivation using the biofloc system in Paccerakkang Village, Makassar City, utilizes tarpaulin ponds to efficiently manage costs and ensure water quality. These ponds are portable, maintain stable temperatures, and offer easier tilapia management than traditional cement ponds. However, farmers face challenges such as limited knowledge and skills in biofloc-based tilapia farming, improper cultivation practices, and inadequate financial management. To address these issues, a community service initiative was implemented, focusing on training, counseling, and guidance in biofloc tilapia farming. The training aimed to enhance participants' understanding of proper seed selection, water quality management, disease prevention, and efficient financial record-keeping. The biofloc system, which transforms fish waste into natural feed through probiotic action, was highlighted as an effective cultivation method. The activity provided hands-on learning and support in the preparation, implementation, and evaluation stages of tilapia farming. As a result, participants gained knowledge and improved practices, leading to better fish growth and increased income. Harvested tilapia are either sold to collectors or consumed by the farmers. This training significantly boosted local participation in biofloc-based tilapia farming and contributed to enhanced community livelihoods